Acute Hyperglycaemia Induces Changes in the Transcription Levels of 4 Major Genes in Human Endothelial Cells: Macroarrays-based Expression Analysis - Chettab, Kamel; Zibara, K.; Belaiba, S.-R.; McGregor, J.L. (Thrombosis and Haemostasis, 2002)
Hyperglycaemia, in insulin-dependent or independent diabetes mellitus, promotes endothelial cell (EC) dysfunction and is a major factor in the development of macro- or microvascular diseases. The mechanisms and the disease-related genes in vascular diseases resulting from hyperglycaemia are poorly understood. Macroarrays, bearing a total of 588 cDNA known genes, were used to analyze HUVEC gene transcription subjected to 25 or 5-mM glucose for 24 h. Isolated mRNA derived from treated first passage HUVEC were reverse transcribed, 32P labeled, and hybridized to the cDNA macroarrays. Results show that acute hyperglycaemia induces an up-regulation of seven major genes, four of which were not previously reported in the literature. Northern blot analyses, performed on these 4 genes, confirm macroarrays results for αv, β4, c-myc, and MUC18. Moreover, time course analysis (0, 2, 4, 8, 12, 16, 24 h) of αv, β4, c-myc, and MUC18 mRNA expression, observed by northern blot assays, showed a peak at time points situated between 2 to 8 h. The 3 other genes (ICAM-1, β1, and IL-8), were shown by others to be significantly upregulated after glucose stimulation. Furthermore, ELISA assays performed on the supernatant of HUVEC culture medium showed a significant increase of IL-8 for cells treated with 25-mM compared to 5-mM glucose. Identified genes, upregulated in endothelial cells as a result of acute hyperglycaemia, may serve as therapeutic or diagnostic targets in vascular lesions present in diabetic patients. These results also demonstrate the use of cDNA macroarrays as an effective approach in identifying genes implicated in a diseased cell.
Keywords: HUVEC; glucose; transcription; macroarray